Home-based treatment of biologics for asthma: who, what, where, when and why. Issue 4 (3rd April 2022) - Menzella, Francesco; Fontana, Matteo; Ruggiero, Patrizia; Livrieri, Francesco; Facciolongo, Nicola
ABSTRACT: Introduction: The advent of biologic therapies for severe asthma has profoundly changed the management of this pathology. The introduction of home administration is therefore an important innovation to optimize the patients' management, even if there are many aspects that need to be clarified and pointed out. Areas covered: This review summarizes the path that led to the possibility of self-administration of biologics, and what the pandemic has changed in the management of these patients. Expert opinion: The growing understanding of asthma phenotypes and endotypes is enabling the careful selection of patients suitable for biologics. In this context, the availability of reliable and simple self-injection devices is important in implementing self-administration. The transition to self-injection is also possible thanks to the high safety profile of biologics. With attention, most patients may potentially be suitable for self-administration. The transition process from hospital to home administration can therefore be carried out correctly by clinicians with adequate expertise in the field of severe asthma and biologic therapies, with the support of other health professionals, pharmacists, and general practitioners. Home administration is probably the best way to guarantee high adherence and high-level satisfaction of patients, even in the long term.